Analysis of Scientific Production published in the journals of the Ecuador collection in SciELO: Trends and Challenges (2014-2022) - Avello-Martínez, Raidell; Gómez Rodriguez, Víctor; Caicedo Quiroz, Rosangela; Tolozano Benites, Roberto; Barzola-Monteses, Julio (Revista General de Información y Documentación, 2025)
This study examines the scientific production of Ecuador in the SciELO network between 2014 and 2022. The main objective is to analyze the temporal evolution, areas of specialization, types of documents, language of publication, international collaboration, and access licenses open in Ecuadorian scientific production. The methodology is based on a cross-sectional descriptive design, using the SciELO Analytics and Analytics Visualizations web tools to collect and analyze data in September 2023. The results reveal a notable increase in the number of documents published over time, indicating a growth and consolidation of Ecuador’s scientific production on the SciELO platform. The areas of Applied Social Sciences and Engineering stand out with a high representation, reflecting the thematic priorities in Ecuadorian research. Most documents are research articles and are published under open-access licenses, promoting the dissemination of research. Ecuador maintains significant international collaborations, which contributes to the visibility of its publications worldwide. Although Spanish is the predominant language, the presence of English and Portuguese demonstrates the openness to global collaboration. The findings highlight progress in Ecuador’s scientific development but also point out the importance of diversifying research areas and further promoting international collaboration to strengthen the country’s scientific presence in the global community.